The climatology and classification of coastal storms on the Southeastern coast of Rio de Janeiro State, Brazil (Ocean and Coastal Research, 2024)
The storm risks in coastal regions have drawn attention worldwide in recent decades. Understanding thecharacteristics and behavior of these events and their potential damage to coasts has become essential fordecision-making and coastal management. This study aimed to identify and examine the climatology of coastalstorms on the central coast of the state of Rio de Janeiro, proposing a classification and a coastal impactevaluation that applies Dolan and Davis’ (1992) storm index. For this, 34 years of NOAA/NCEP/NCAR hindcastwave database were used (1979 - 2013). Secondarily, this study aimed to compare wave data at two locations(the south-orientated west and the east-northeast-orientated east coasts) to verify the influence of coastalorientation against storm events. This research found 231 storm events on the west coast and 44 on the eastcoast. While mean durations resembled each other (at around 27 hours), the east coast had a 9% lower meanstorm wave height. The storm peak direction from the south predominated on the west coast (52%), whereas asouth-southeast direction dominated the east coast (50%). Storm classification showed 3.4 and 9% of stormsconsidered Extreme in the west and east, respectively. Extreme storms include those in September 1983, May1997, May 2001, and April 2010. Coastal storms on the west and east represented 2.39 and 0.57% of allcyclones identified in the southwestern Atlantic. In shallow waters, the highest amount of energy dissipationoccurred on the east coast, which is sheltered from storms from the south-southwest but is exposed to thosefrom the south-southeast. Extreme and Severe events greatly impacted the coast, including beach and duneerosion, overwash, and property damage. However, even coastal storms considered Weak caused considerablecoastal damage.